Food systems in Latin America and the Caribbean: Challenges in a post-pandemic world - Graziano da Silva, Silva; Jales, Mario; Rapallo, Ricardo; Díaz-Bonilla, Eugenio; Girardi, Guido; del Grossi, Mauro (Food and Agricultural Organization of the United Nations, 2021)
The book has been prepared by authors from different international organizations – including FAO, IFPRI, UNCTAD and ECLAC, as well as legislators and academics from prestigious Latin American universities – seeking to foster reflections for the Global Food Systems Summit, to be held in September 2021. It contextualizes the region’s food systems within a post COVID-19 pandemic scenario and raises new challenges (and opportunities) for makers, decision makers, the private sector, and the general public. Likewise, it offers important reflections on sustainability, from production to consumption, with the call to promote better governance of the global and regional food system. In order to face what some authors have deemed “the Syndemic of the century”, the participation of companies, research centres, academia, NGOs, government agencies and international organizations will be necessary.